Effectiveness of influence of pre-sowing seeds treatment with combinations metabolically active compounds on biochemical composition of soybean grain - Koziuchko, Alona; Козючко, Альона; Havii, Valentyna; Гавій, Валентина; Kuchmenko, Olena; Кучменко, Олена; Sheiko, Vitalii; Шейко, Віталій; Machulskyi, Hryhorii; Мачульський, Григорій; Novikova, Anna; Новікова, Анна; et al. (Державний природознавчий музей НАН України, 2024)
Soybean is the most valuable crop of all leguminous crops. Soy excels in terms of the content of vital substances in the grain. It is characterized by a high content of protein, oil and high nutritional qualities. Treatment of seeds with vitamin E in combination with ubiquinone-10 before sowing provided an increase in crude protein content in soybean seeds by an average of 31.44%. During pre-sowing treatment with a combination of vitamin E+ ubiquinone-10, an increase in the content of carotenoids was observed by an average of 45.65% compared to the control and by 43.48% according to the Vympel. The content of mono- and disaccharides increased with pre-sowing treatment with vitamin E and ubiquinone-10. The combination of vitamin E and ubiquinone-10, in comparison with other research options, proved to be the most effective when studying the biochemical composition of soybean seeds. Соя – найцінніша культура з усіх зернобобових. За вмістом життєво важливих речовин у зерні виділяється соя. Характеризується високим вмістом білка, олії та високими поживними якостями. Обробка насіння вітаміном Е в поєднанні з убіхіноном-10 перед посівом забезпечила підвищення вмісту сирого протеїну в насінні сої в середньому на 31,44 %. При передпосівній обробці комбінацією вітамін Е+убіхінон-10 спостерігалося підвищення вмісту каротиноїдів у середньому на 45,65 % порівняно з контролем і на 43,48 % за Вимпелом. Вміст моно- та дисахаридів підвищувався за передпосівної обробки вітаміном Е та убіхіноном-10. Комбінація вітаміну Е та убіхінону-10, порівняно з іншими варіантами досліджень, виявилася найбільш ефективною при вивченні біохімічного складу насіння сої.
Ефективність впливу передпосівної обробки насіння комбінаціями метаболічно активних речовин на біохімічний склад зерна сої
Keywords: Soy; Соя; Biochemical composition; Біохімічний склад; Crude protein; Сирий білок; mono- and disaccharides; моно- та дисахариди; carotenoids; каротиноїди; Vitamin E; Вітамін Е; Ubiquinone-10; Убіхінон-10; 4-hydroxibenzoic Acid (PHBA); гідроксибензойна кислота (PHBA); Methionin; Метіонін; Magnesium sulfate (MgSO4); Сульфат магнію (MgSO4); Vympel; Вимпел